Conservation beyond protected areas: Understanding stakeholder perspectives on other effective area-based conservation measures - Alanna Marsh; Carly N. Cook (Ambio, 2026)
Other effective area-based conservation measures (OECMs) serve as an important tool to recognise diverse areas for their contributions to conservation, yet implementation remains slow. A key barrier to implementation is the lack of engagement with stakeholders who manage these areas and thus uncertainty about how best to secure their participation. We interviewed stakeholders representing different land uses that could be candidate OECMs in Australia, to capture their perspectives on OECMs and the factors that may motivate or deter their engagement. Stakeholder responses revealed an openness to and interest in OECMs, although many questions that are critical to their participation were raised. Concerns around long-term obligations and conflict between different management objectives were recurrent limitations to engagement. The opportunity for wider recognition of conservation efforts and increased social licence were key motivating factors. Important differences between stakeholder groups indicate that tailored strategies may improve engagement, which is a critical step in progressing OECMs.

Lessons learned from screening potential other effective area‐based conservation measures - Carly N. Cook; Madhu Rao; Peter J. Clyne; Vanessa Rathbone; Christian Barrientos; Antonio Boveda; Alex Diment; Jorge Parra; Valeria Falabella; Matthew Linke; Deo Kujirakwinja; Stephane Ostrowski; et al. (Conservation Biology, 2026)
Other effective area‐based conservation measures (OECMs) are sites that deliver effective biodiversity outcomes irrespective of their management objectives. These areas are widely expected to play an important role in efforts to protect 30% of Earth by 2030. Despite general guidance to support screening sites against the formal criteria to be OECMs, progress recognizing sites has been limited. To advance the ability to identify OECMs, we developed a questionnaire that translates the components of the broad formal guidance into statements that experts can use to screen potential OECMs. Twenty‐eight local experts used the questionnaire to evaluate a large global sample of 81 sites. Most sites evaluated were largely in good condition and had the potential to achieve conservation outcomes, but none met the criteria to be considered OECMs. The most common challenges are related to threat management, adequate resourcing, and the ability to demonstrate that governance and management are achieving effective and sustained conservation outcomes. Based on the formal International Union for Conservation of Nature guidance, sites that only partially meet the relevant criteria remain candidate OECMs. Our questionnaire provides a nuanced way to assess OECMs that can help identify what support sites need to meet the necessary criteria. With effective long‐term conservation outcomes unable to be demonstrated for so many important conservation areas, our findings raise important questions about how to ensure area‐based conservation promotes positive and sustained outcomes for biodiversity.

Imperfect detection of terrestrial mammals in environmental impact assessment (EIA) baseline surveys may compromise decision-making and mitigation measures - Amanda M.S. Dias; Carly Cook; Adriano Pereira Paglia; Rodrigo Lima Massara (Environmental Impact Assessment Review, 2025)

Monitoring for the presence of invasive arboreal rodents: an assessment of monitoring tools across forest strata - Alexandra H. Nance; Melinda Wilson; Carly N. Cook; Rohan H. Clarke (Biological Invasions, 2024)

Species and ecological communities as management surrogates for threatened biodiversity - Javiera Olivares-Rojas; Carly N. Cook; Michelle S. Ward; Jessica C. Walsh (Biodiversity and Conservation, 2024)
In the face of the ongoing biodiversity crisis and limited conservation funding, surrogate approaches have become a valuable tool to represent biodiversity. Management surrogates are those that indirectly benefit an ecological system or species by representing the management requirements of co-occurring biodiversity. Recent findings highlight the cost-effective potential of surrogate species in managing threatened species, however, evaluating higher levels of biodiversity as management surrogates remains unexplored. Here, we sought to maximize conservation outcomes for threatened species and threatened ecological communities (TECs) by prioritizing management based on overlapping distributions, threats, and costs. We describe a prioritization framework for identifying TECs that could serve as cost-effective surrogates, and compare it with prioritizing threatened species only or both species and TECs. We show that when the objective is to maximize benefits for threatened species, a community approach performs poorly due to limited geographic overlap and high costs, while prioritizing species returned 7.5 times more benefits delivered to species under the same budget. Yet, if the objective is to maximize benefits across species and TECs simultaneously, a combined approach including both as surrogates delivers the greatest benefit for the same costs as a species-only approach. Range sizes and taxonomic groups significantly influenced the priority list, with threatened invertebrates and TECs of smaller ranges more likely to be selected as surrogates. Overall, this study emphasizes the importance of incorporating accurate data on factors such as threats and costs for identifying effective management surrogates, and highlights the potential benefits of prioritizing across multiple biodiversity features.

Progress developing the concept of other effective area‐based conservation measures - Carly N. Cook (Conservation Biology, 2024)
In 2010, the introduction of other effective area‐based conservation measures (OECMs) into international policy caused a paradigm shift in area‐based conservation, which included consideration of areas outside formal protected areas and places where biodiversity conservation may not be a management objective for the site. Despite the importance of this shift for global conservation, conservation science and policy have been slow to engage with the concept of OECMs. As the world moves toward protecting 30% of the Earth by 2030, it is imperative to develop evidence‐based guidance for how to identify effective conservation measures, especially tools to help evaluate and monitor the biodiversity outcomes associated with potential OECMs. To understand the current progress in developing the concept of OECMs, I evaluated the peer‐reviewed literature to consolidate and synthesize current knowledge. I conducted a thematic analysis of papers to identify the types of challenges and opportunities being discussed and lessons from studies evaluating the effectiveness of OECMs. Only 105 studies mentioned OECMs, and those that did rarely move beyond superficial mention of OECMs as part of area‐based conservation. Around one‐half of studies listed potential risks or benefits of OECMs but none provided evidence these issues have materialized. Twenty‐three studies attempted to identify potential OECMs, although specific case studies were rare. The 7 studies that evaluated existing OECMs were highly critical of how they had been implemented to date. Studies that evaluated conservation outcomes were extremely rare, and suggested effectiveness must be judged on a case‐by‐case basis. The current literature not only leaves many gaps in the science required to operationalize the concept of OECMs, but also often raises additional questions that need to be addressed. If these gaps are not filled by robust science, the promised benefits for biodiversity from OECMs may never be realized.

Foresight science in conservation: Tools, barriers, and mainstreaming opportunities - Gabrielle Ednie; Tyreen Kapoor; Olga Koppel; Morgan L. Piczak; Jessica L. Reid; Alyssa D. Murdoch; Carly N. Cook; William J. Sutherland; Steven J. Cooke (Ambio, 2023)

Defining performance thresholds for effective management of biodiversity within protected areas - Mairi Hilton; Carly N. Cook (Conservation Biology, 2022)
Performance thresholds are an important tool for determining successful conservation outcomes. They provide an objective means of defining good ecological condition and have been endorsed as an essential part of best practice in protected area (PA) management within the International Union for the Conservation of Nature Green List of Protected and Conserved Areas Standard. With a growing number of PAs attaining Green List status globally, thresholds developed by PAs on the Green List present an excellent resource with which to identify the attributes of well‐defined performance thresholds. We examined 349 thresholds associated with PAs on the Green List to determine whether they were specific and measurable (i.e., factors recognized as essential for setting well‐defined targets). We assessed whether thresholds were defined quantitatively and whether definitions included ambiguous terms (e.g., stable numbers ). We identified six different ways thresholds were expressed and found that many thresholds were expressed as management objectives, rather than ecological condition thresholds, although this trend improved over time. Approximately one‐half of the performance thresholds lacked the necessary specificity to delineate successful outcomes. Our results enabled us to develop a checklist of information required to set robust performance thresholds. Recommendations include that thresholds should be quantitatively defined, including quantitative estimates of the limits of acceptable change (LAC) around the target condition. To ensure transparency, a rationale and associated evidence should be provided to support the threshold and the LAC. When accompanied by a rationale and quantitative estimate of the current condition of the value, unambiguously defined thresholds with a quantitative LAC provide an objective means of demonstrating that successful conservation outcomes have been achieved. These recommendations will help conservation managers apply the Green List Standard and improve the measurement of conservation outcomes more broadly.

Cooperative breeding and the emergence of multilevel societies in birds - Ettore Camerlenghi; Alexandra McQueen; Kaspar Delhey; Carly N. Cook; Sjouke A. Kingma; Damien R. Farine; Anne Peters (Ecology Letters, 2022)
Multilevel societies (MLSs), where social levels are hierarchically nested within each other, are considered one of the most complex forms of animal societies. Although thought to mainly occurs in mammals, it is suggested that MLSs could be under‐detected in birds. Here, we propose that the emergence of MLSs could be common in cooperatively breeding birds, as both systems are favoured by similar ecological and social drivers. We first investigate this proposition by systematically comparing evidence for multilevel social structure in cooperative and non‐cooperative birds in Australia and New Zealand, a global hotspot for cooperative breeding. We then analyse non‐breeding social networks of cooperatively breeding superb fairy‐wrens ( Malurus cyaneus ) to reveal their structured multilevel society, with three hierarchical social levels that are stable across years. Our results confirm recent predictions that MLSs are likely to be widespread in birds and suggest that these societies could be particularly common in cooperatively breeding birds.

Lessons from other disciplines for setting management thresholds for biodiversity conservation - Mairi Hilton; Jessica C. Walsh; Erin Liddell; Carly N. Cook (Conservation Biology, 2022)
Successful, state‐dependent management, in which the goal of management is to maintain a system in a desired state, involves defining the boundaries between different states. Once these boundaries have been defined, managers require a strategic action plan with thresholds that initiate management interventions to either maintain or return the system to a desired state. This approach to management is widely used across diverse industries from agriculture, to medicine, to information technology, but it has only been adopted in conservation management relatively recently. Conservation practitioners have expressed a willingness to integrate this structured approach in their management systems, but they have also voiced concerns, including lack of a robust process for doing so. Given the widespread use of state‐dependent management in other fields, we conducted an extensive review of the literature on threshold‐based management to gain insight into how and where it is applied and identify potential lessons for conservation management. We identified 22 industries using 75 different methods for setting management thresholds in 843 studies. Methods spanned six broad approaches, including expert driven, statistical, predictive, optimization, experimental, and artificial intelligence methods. The objectives of each of these studies influenced the approaches used, including the methods for setting thresholds and selecting actions, and the number of thresholds set. The role of value judgments in setting thresholds was clear; studies across all industries frequently involved experts in setting thresholds, often accompanied by computational tools to simulate the consequences of proposed thresholds under different conditions. Of the 30 conservation studies examined, two‐thirds used expert‐driven methods, consistent with prior evidence that experience‐based information often drives conservation management decisions. The methods we identified from other disciplines could help conservation decision makers set thresholds for management interventions in different contexts, linking monitoring to management actions and ensuring that conservation interventions are timely and effective.

Assessing the current state of ecological connectivity in a large marine protected area system - Kelsey E. Roberts; Carly N. Cook; Jutta Beher; Eric A. Treml (Conservation Biology, 2021)
The establishment of marine protected areas (MPAs) is a critical step in ensuring the continued persistence of marine biodiversity. Although the area protected in MPAs is growing, the movement of individuals (or larvae) among MPAs, termed connectivity, has only recently been included as an objective of many MPAs. As such, assessing connectivity is often neglected or oversimplified in the planning process. For promoting population persistence, it is important to ensure that protected areas in a system are functionally connected through dispersal or adult movement. We devised a multi‐species model of larval dispersal for the Australian marine environment to evaluate how much local scale connectivity is protected in MPAs and determine whether the extensive system of MPAs truly functions as a network. We focused on non‐migratory species with simplified larval behaviors (i.e., passive larval dispersal) (e.g., no explicit vertical migration) as an illustration. Of all the MPAs analyzed (approximately 2.7 million km 2 ), outside the Great Barrier Reef and Ningaloo Reef,

Tackling the tide: A rapid assessment protocol to detect terrestrial vertebrates in mangrove forests - Stefanie M. Rog; Rohan H. Clarke; Ernest Minnema; Carly N. Cook (Biodiversity and Conservation, 2020)

The case for embedding researchers in conservation agencies - Dirk J. Roux; Richard T. Kingsford; Carly N. Cook; Jane Carruthers; Katrina Dickson; Marc Hockings (Conservation Biology, 2019)
Although protected areas represent a pivotal response to escalating anthropogenic threats, they face many pressures, inside and outside their boundaries. Amid these challenges, effective conservation is guided by evidence‐based decision making supported by dynamic processes of learning and knowledge exchange. Although different models promote knowledge exchange, embedding research scientists within conservation agencies is best suited to supporting evidence‐based conservation. Based on available literature and our experiences on several continents, we considered the benefits, challenges, and opportunities associated with embedding research scientists within conservation agencies and the research required to better understand the effectiveness of the embedding model for evidence‐based conservation. Embedded researchers provide long‐term commitment to building social capital among academic and nonacademic stakeholders; act as skilled gatekeepers who increase 2‐way flow of knowledge between scientists and managers; attract, coordinate, and support management‐relevant external research projects; drive the design and maintenance of long‐term monitoring; and align their research with information needs. Notwithstanding the many benefits, research capacity of conservation agencies is declining worldwide. A significant challenge is that the values, structures, functions, and effectiveness of the embedding model of knowledge exchange remain poorly evaluated and documented. Also, embedded researchers have to balance their desire for creativity and flexibility with the standardization and quality control required by their public sector agencies; may be perceived as not credible because they are not truly independent of their agency; and have to couple scientific productivity with skills for transdisciplinary research, social facilitation, and stakeholder engagement. Systematic research on embedding and other models of knowledge exchange, across different world contexts, is required to better understand the benefits, costs, and institutional arrangements associated with different models.

Protected area downgrading, downsizing, and degazettement as a threat to iconic protected areas - Siyu Qin; Rachel E. Golden Kroner; Carly Cook; Anteneh T. Tesfaw; Rowan Braybrook; Carlos Manuel Rodriguez; Claire Poelking; Michael B. Mascia (Conservation Biology, 2019)
Protected areas (PAs) are expected to conserve nature and provide ecosystem services in perpetuity, yet widespread protected area downgrading, downsizing, and degazettement (PADDD) may compromise these objectives. Even iconic protected areas are vulnerable to PADDD, although these PADDD events are often unrecognized. We identified 23 enacted and proposed PADDD events within World Natural Heritage Sites and examined the history, context, and consequences of PADDD events in 4 iconic PAs (Yosemite National Park, Arabian Oryx Sanctuary, Yasuní National Park, and Virunga National Park). Based on insights from published research and international workshops, these 4 cases revealed the diverse pressures brought on by competing interests to develop or exploit natural landscapes and the variety of mechanisms that enables PADDD. Knowledge gaps exist in understanding of the conditions through which development pressures translate to PADDD events and their impacts, partially due to a lack of comprehensive PADDD records. Future research priorities should include comprehensive regional and country‐level profiles and analysis of risks, impacts, and contextual factors related to PADDD. Policy options to better govern PADDD include improving tracking and reporting of PADDD events, establishing transparent PADDD policy processes, coordinating among legal frameworks, and mitigating negative impacts of PADDD. To support PADDD research and policy reforms, enhanced human and financial capacities are needed to train local researchers and to host publicly accessible data. As the conservation community considers the achievements of Aichi Target 11 and moves toward new biodiversity targets beyond 2020, researchers, practitioners, and policy makers need to work together to better track, assess, and govern PADDD globally.

Improving conservation practice with principles and tools from systems thinking and evaluation - Andrew T. Knight; Carly N. Cook; Kent H. Redford; Duan Biggs; Claudia Romero; Alejandro Ortega-Argueta; Cameron D. Norman; Beverly Parsons; Martin Reynolds; Glenda Eoyang; Matt Keene (Sustainability Science, 2019)

Conservation practitioners’ understanding of how to manage evolutionary processes - Carly N. Cook; Carla M. Sgrò (Conservation Biology, 2019)
Both academics and practitioners consider a lack of knowledge about evolutionary theory to be a general barrier to effectively managing genetic diversity. However, it is challenging to judge practitioners’ level of understanding and how this influences their management decisions. Knowledge built through experience may be difficult for practitioners to articulate, but could nonetheless result in appropriate management strategies. To date, researchers have assessed only the explicit (formal) knowledge practitioners have of evolutionary concepts. To explore practitioners’ understanding of evolutionary concepts, it is necessary to consider how they might apply explicit and implicit knowledge to their management decisions. Using an online survey, we asked Australian practitioners to respond to 2 common management scenarios in which there is strong evidence that managing genetic diversity can improve outcomes: managing small, isolated populations and sourcing seeds for restoration projects. In describing their approach to these scenarios, practitioners demonstrated a stronger understanding of the effective management of genetic diversity than the definitions of the relevant concepts. However, their management of genetic diversity within small populations was closer to best practice than for restoration projects. Moreover, the risks practitioners described in implementing best practice management were more likely to affect their approach to restoration than translocation projects. These findings provide evidence that strategies to build the capacity of practitioners to manage genetic diversity should focus on realistic management scenarios. Given that practitioners recognize the importance of adapting their practices and the strong evidence for the benefits of actively managing genetic diversity, there is hope that better engagement by evolutionary biologists with practitioners could facilitate significant shifts toward evolutionarily enlightened management.

Using social‐network research to improve outcomes in natural resource management - Julie E. Groce; Megan A. Farrelly; Bradley S. Jorgensen; Carly N. Cook (Conservation Biology, 2019)
The conservation and management of natural resources operates in social–ecological systems in which resource users are embedded in social and environmental contexts that influence their management decisions. Characterizing social networks of resource users can be used to inform understanding of social influences on decision making, and social network analysis (SNA) has emerged as a useful technique to explore these relationships. We synthesized how SNA has been used in 85 studies of natural resource management. We considered how social networks and social processes (e.g., interactions between individuals) influence each other and in turn influence social outcomes (e.g., decisions or actions) that affect environmental outcomes (e.g., improved condition). Descriptive methods were used in 58% of the studies to characterize social processes, and 42% of the studies compared multiple networks or multiple points in time to assess social or environmental outcomes. In 4 studies, authors assessed network interventions intended to affect social processes or environmental outcomes. The heterogeneity in case studies, methods, and analyses preclude general lessons. Thus, to structure and further learning about the role of social networks in achieving environmental outcomes, we created a typology that deconstructs social processes, social outcomes, and environmental outcomes into themes and options of social and ecological measures within each. We suggest shifts in research foci toward intervention studies to aid in understanding causality and inform the design of conservation initiatives. There is a need to develop clearer justification and guidance around the proliferation of network measures. The use of SNA in natural resource management is expanding rapidly; thus, now is the time for the conservation community to build a more rigorous evidence base to demonstrate the extent to which social networks can play a role in achieving desired social and environmental outcomes.

Standardized reporting of the costs of management interventions for biodiversity conservation - Gwenllian D. Iacona; William J. Sutherland; Bonnie Mappin; Vanessa M. Adams; Paul R. Armsworth; Tim Coleshaw; Carly Cook; Ian Craigie; Lynn V. Dicks; James A. Fitzsimons; Jennifer McGowan; Andrew J. Plumptre; et al. (Conservation Biology, 2018)
Effective conservation management interventions must combat threats and deliver benefits at costs that can be achieved within limited budgets. Considerable effort has focused on measuring the potential benefits of conservation interventions, but explicit quantification of the financial costs of implementation is rare. Even when costs have been quantified, haphazard and inconsistent reporting means published values are difficult to interpret. This reporting deficiency hinders progress toward a collective understanding of the financial costs of management interventions across projects and thus limits the ability to identify efficient solutions to conservation problems or attract adequate funding. We devised a standardized approach to describing financial costs reported for conservation interventions. The standards call for researchers and practitioners to describe the objective and outcome, context and methods, and scale of costed interventions, and to state which categories of costs are included and the currency and date for reported costs. These standards aim to provide enough contextual information that readers and future users can interpret the cost data appropriately. We suggest these standards be adopted by major conservation organizations, conservation science institutions, and journals so that cost reporting is comparable among studies. This would support shared learning and enhance the ability to identify and perform cost‐effective conservation.

Quantifying the extent of protected‐area downgrading, downsizing, and degazettement in Australia - Carly N. Cook; Rebecca S. Valkan; Michael B. Mascia; Melodie A. McGeoch (Conservation Biology, 2017)
The use of total area protected as the predominant indicator of progress in building protected area (PA) networks is receiving growing criticism. Documenting the full dynamics of PA networks, both in terms of the gains and losses in protection, provides a much more informative approach to tracking progress. To this end, documentation of PA downgrading, downsizing, and degazettement (PADDD) has increased. Studies of PADDD events generally fail to place these losses in the context of gains in protection; therefore, they omit important elements of PA network dynamics. To address this limitation, we used a spatially explicit approach to identify every parcel of land added to and excised from the Australian terrestrial PA network and PAs that had their level of protection changed over 17 years (1997–2014). By quantifying changes in the spatial configuration of the PA network with time‐series data (spatial layers for nine separate time steps), ours is the first assessment of the dynamics (increases and decreases in area and level of protection) of a PA network and the first comprehensive assessment of PADDD in a developed country. We found that the Australian network was highly dynamic; there were 5233 changes in area or level of protection over 17 years. Against a background of enormous increases in area protected, we identified over 1500 PADDD events, which affected over one‐third of the network, which were largely the result of widespread downgrading of protection. We believe our approach provides a mechanism for robust tracking of trends in the world's PAs through the use of data from the World Database on Protected Areas. However, this will require greater transparency and improved data standards in reporting changes to PAs.

Aligning science and policy to achieve evolutionarily enlightened conservation - Carly N. Cook; Carla M. Sgrò (Conservation Biology, 2017)
There is increasing recognition among conservation scientists that long‐term conservation outcomes could be improved through better integration of evolutionary theory into management practices. Despite concerns that the importance of key concepts emerging from evolutionary theory (i.e., evolutionary principles and processes) are not being recognized by managers, there has been little effort to determine the level of integration of evolutionary theory into conservation policy and practice. We assessed conservation policy at 3 scales (international, national, and provincial) on 3 continents to quantify the degree to which key evolutionary concepts, such as genetic diversity and gene flow, are being incorporated into conservation practice. We also evaluated the availability of clear guidance within the applied evolutionary biology literature as to how managers can change their management practices to achieve better conservation outcomes. Despite widespread recognition of the importance of maintaining genetic diversity, conservation policies provide little guidance about how this can be achieved in practice and other relevant evolutionary concepts, such as inbreeding depression, are mentioned rarely. In some cases the poor integration of evolutionary concepts into management reflects a lack of decision‐support tools in the literature. Where these tools are available, such as risk‐assessment frameworks, they are not being adopted by conservation policy makers, suggesting that the availability of a strong evidence base is not the only barrier to evolutionarily enlightened management. We believe there is a clear need for more engagement by evolutionary biologists with policy makers to develop practical guidelines that will help managers make changes to conservation practice. There is also an urgent need for more research to better understand the barriers to and opportunities for incorporating evolutionary theory into conservation practice.

Much more give than take: South Africa as a major donor but infrequent recipient of invasive non‐native grasses - Vernon Visser; John R. U. Wilson; Lyn Fish; Carly Brown; Garry D. Cook; David M. Richardson (Global Ecology and Biogeography, 2016)
Aim Some regions donate more invaders from particular taxonomic and functional groups than they receive. We demonstrate a particularly striking donor–recipient asymmetry in invasion ecology in grasses. Specifically, we explore whether low numbers of invasive grasses in South Africa can be explained by sampling biases, introduction dynamics, species traits or invasibility of ecosystems. Location South Africa, Australia, Chile, Europe and the USA. Methods We tested for a donor–recipient asymmetry using lists of native and non‐native grasses in five regions across the globe. Then, using distribution, trait and environmental data, we tested whether regions differed in: (1) herbarium sampling effort; (2) introduction dynamics of non‐native grasses (primary uses, area of origin and minimum residence time of non‐native grasses); (3) traits of native and non‐native grasses (leaf size, height, life history, growth form, C 3 :C 4 ratio and taxonomic placement); and (4) fire frequency. Results South Africa has fewer invasive grasses, and fewer widespread invasive grasses, than other regions; while grasses native to South Africa are much more likely to be invasive elsewhere than other grasses. This asymmetry cannot be explained by sampling biases, historical trade links or minimum residence time. Rather it is likely to be due to a combination of: (1) the massive scale of the introduction of South African grasses around the world; (2) specific traits that make South African grasses successful competitors; and (3) the high fire frequency of many South African ecosystems to which many native grasses are adapted, but introduced grasses are not. Main conclusion South Africa has a high diversity of grasses that possess specific traits to cope with fire, grazing and disturbance. This makes them more competitive. Moreover, the high diversity of certain grass lineages in South Africa acts as a reservoir of potential invaders and possibly helps limit invasions in South Africa by promoting fire.

Using Strategic Foresight to Assess Conservation Opportunity - CARLY N. COOK; BONNIE C. WINTLE; STEPHEN C. ALDRICH; BRENDAN A. WINTLE (Conservation Biology, 2014)
The nature of conservation challenges can foster a reactive, rather than proactive approach to decision making. Failure to anticipate problems before they escalate results in the need for more costly and time‐consuming solutions. Proactive conservation requires forward‐looking approaches to decision making that consider possible futures without being overly constrained by the past. Strategic foresight provides a structured process for considering the most desirable future and for mapping the most efficient and effective approaches to promoting that future with tools that facilitate creative thinking. The process involves 6 steps: setting the scope, collecting inputs, analyzing signals, interpreting the information, determining how to act, and implementing the outcomes. Strategic foresight is ideal for seeking, recognizing, and realizing conservation opportunities because it explicitly encourages a broad‐minded, forward‐looking perspective on an issue. Despite its potential value, the foresight process is rarely used to address conservation issues, and previous attempts have generally failed to influence policy. We present the strategic foresight process as it can be used for proactive conservation planning, describing some of the key tools in the foresight tool kit and how they can be used to identify and exploit different types of conservation opportunities. Scanning is an important tool for collecting and organizing diverse streams of information and can be used to recognize new opportunities and those that could be created. Scenario planning explores how current trends, drivers of change, and key uncertainties might influence the future and can be used to identify barriers to opportunities. Backcasting is used to map out a path to a goal and can determine how to remove barriers to opportunities. We highlight how the foresight process was used to identify conservation opportunities during the development of a strategic plan to address climate change in New York State. The plan identified solutions that should be effective across a range of possible futures. Illustrating the application of strategic foresight to identify conservation opportunities should provide the impetus for decision makers to explore strategic foresight as a way to support more proactive conservation policy, planning, and management.

Contribution of Systematic Reviews to Management Decisions - CARLY N. COOK; HUGH P. POSSINGHAM; RICHARD A. FULLER (Conservation Biology, 2013)
Systematic reviews comprehensively summarize evidence about the effectiveness of conservation interventions. We investigated the contribution to management decisions made by this growing body of literature. We identified 43 systematic reviews of conservation evidence, 23 of which drew some concrete conclusions relevant to management. Most reviews addressed conservation interventions relevant to policy decisions; only 35% considered practical on‐the‐ground management interventions. The majority of reviews covered only a small fraction of the geographic and taxonomic breadth they aimed to address (median = 13% of relevant countries and 16% of relevant taxa). The likelihood that reviews contained at least some implications for management tended to increase as geographic coverage increased and to decline as taxonomic breadth increased. These results suggest the breadth of a systematic review requires careful consideration. Reviews identified a mean of 312 relevant primary studies but excluded 88% of these because of deficiencies in design or a failure to meet other inclusion criteria. Reviews summarized on average 284 data sets and 112 years of research activity, yet the likelihood that their results had at least some implications for management did not increase as the amount of primary research summarized increased. In some cases, conclusions were elusive despite the inclusion of hundreds of data sets and years of cumulative research activity. Systematic reviews are an important part of the conservation decision making tool kit, although we believe the benefits of systematic reviews could be significantly enhanced by increasing the number of reviews focused on questions of direct relevance to on‐the‐ground managers; defining a more focused geographic and taxonomic breadth that better reflects available data; including a broader range of evidence types; and appraising the cost‐effectiveness of interventions. Contribuciones de las Revisiones Sistemáticas a las Decisiones de Manejo

Achieving Conservation Science that Bridges the Knowledge–Action Boundary - CARLY N. COOK; MICHAEL B. MASCIA; MARK W. SCHWARTZ; HUGH P. POSSINGHAM; RICHARD A. FULLER (Conservation Biology, 2013)
There are many barriers to using science to inform conservation policy and practice. Conservation scientists wishing to produce management‐relevant science must balance this goal with the imperative of demonstrating novelty and rigor in their science. Decision makers seeking to make evidence‐based decisions must balance a desire for knowledge with the need to act despite uncertainty. Generating science that will effectively inform management decisions requires that the production of information (the components of knowledge) be salient (relevant and timely), credible (authoritative, believable, and trusted), and legitimate (developed via a process that considers the values and perspectives of all relevant actors) in the eyes of both researchers and decision makers. We perceive 3 key challenges for those hoping to generate conservation science that achieves all 3 of these information characteristics. First, scientific and management audiences can have contrasting perceptions about the salience of research. Second, the pursuit of scientific credibility can come at the cost of salience and legitimacy in the eyes of decision makers, and, third, different actors can have conflicting views about what constitutes legitimate information. We highlight 4 institutional frameworks that can facilitate science that will inform management: boundary organizations (environmental organizations that span the boundary between science and management), research scientists embedded in resource management agencies, formal links between decision makers and scientists at research‐focused institutions, and training programs for conservation professionals. Although these are not the only approaches to generating boundary‐spanning science, nor are they mutually exclusive, they provide mechanisms for promoting communication, translation, and mediation across the knowledge–action boundary. We believe that despite the challenges, conservation science should strive to be a boundary science, which both advances scientific understanding and contributes to decision making. Logrando que la Ciencia de la Conservación Trasponga la Frontera Conocimiento‐Acción

Accountability, Reporting, or Management Improvement? Development of a State of the Parks Assessment System in New South Wales, Australia - Marc Hockings; Carly N. Cook; R. W. Carter; Robyn James (Environmental Management, 2009)